Health promotion: the conception among nurses working in the Family Health Program - Priscila Araújo Rocha; Teresa Cristina Soares; Beatriz Francisco Farah; Denise Barbosa de Castro Friedrich (Revista Brasileira em Promoção da Saúde, 2012)
Objective: To investigate the conception of Health Promotion among nurses working in the Family Health Program. Methods: This was a qualitative descriptive study, conducted in five Primary Health Care Units that are connected to the Family Health Program, in the city of Juiz de Fora - MG, Brazil, from March to April, 2010. Subjects were five nurses, one from each participating unit, randomly selected, according to their availability and acceptance to participate in the study. Data collection used semi-structured interview technique. The speeches were analyzed using thematic analysis. Results: From the analysis of the speeches it was evident that nurses misunderstand health promotion and prevention. They unanimously cited the role of educator played by nurses. Conclusion: The nurses were found to have a distorted conception of health promotion and health practices are still developed based on a preventive approach. Concept of health promotion generates questions among the studied group, therefore, it should be more discussed by nurses.